Phase calibration for ideal wideband chirp in satellite-based synthetic aperture radar - Kim, Kyeongrok; Kang, Junghwa; Kim, Jae Hyun (ICT Express, 2022)
With the development of launch vehicles, the number of satellite-based synthetic aperture radar (SAR) has been increasing. Satellite-based SAR can acquire high-resolution images at day and night regardless of the weather. Since SAR resolution is determined by a chirp bandwidth, corresponding a generation technology of wideband chirp is essentially required for high-resolution SAR images under consideration of relatively small and light weight SAR system. Therefore, an ideal chirp waveform generation, which is challenging task in actual hardware, is proposed by modifying a chirp equation for phase calibration, and is verified based on Sentinel-1 satellite SAR parameters. The proposed method is applied to our SAR hardware and we confirm the calibrated waveform. Evaluation results using SAR observation simulation show that the impulse response with the proposed method has better performances.
Keywords: Chirp pulse signal; Impulse response; Phase calibration; Small satellite; Synthetic aperture radar (SAR)